RUSSIAN LANGUAGE IN THE AGRARIAN SPHERE: FEATURES, TERMINOLOGY AND COMMUNICATION - Хушбоков Бахтияр Буриевич преподаватель; Жумаева Шахло Чориевна (Web of Journals Publishing, 2025)
The article is devoted to the study of the features of the Russian language in agriculture, including its terminology and role in professional communication. The main categories of agricultural terms, including concepts related to crop production, animal husbandry and agrotechnical processes, are considered. Characteristics of the language of the industry, such as borrowing, professional jargon and dialectics, are analyzed. Particular attention is paid to the role of the Russian language in scientific, industrial and business contacts in agriculture. The current trends of the development of agricultural terminology resulting from technological development and globalization are defined.
Keywords: Russian language, agrarian sphere, agriculture, terminology, professional communication, agriculture.